Remarks on the Real-Utopia Project: the contribution of an emancipatory social science - Souza, Marcela Fernanda da Paz de (Interações, 2017)
Interview: Erik Olin Wright Professor of Sociology at the University of Wisconsin (Madison) and former President of the American Association of Sociology, 2011-2012 By: Marcela Fernanda da Paz de Souza Post-doctorate in Urban and Regional Studies (PNPD / UFRN) and PhD in Social Sciences (UFJF).Research Inequalities, Sociology of Work and Methodology.